Low seropositivity for SARS-CoV-2 antibodies among healthcare workers after the first COVID-19 pandemic wave in Greece. (September 2021) - Galanis, P.; Kaitelidou, D.; Prezerakos, P.; Kotsiopoulos, I.; Siskou, O.; Konstantakopoulou, O.; Hadjichristodoulou, C.; Tsiodras, S.
Abstract: Objectives: To estimate the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) seropositivity among healthcare workers (HCWs) in Greece and to identify high-risk groups in healthcare facilities. Study design: The study design used in this study is a nationwide cross-sectional study. Methods: Data were collected from 1 June to 9 July 2020. HCWs in the Greek National Health System were offered a free SARS-CoV-2 IgG antibody test, regardless of symptoms. Results: Overall, 379 of 57, 418 HCWs (0.66%, 95% confidence interval [CI]: 0.59–0.73) were positive for SARS-CoV-2 antibodies. The adjusted overall seroprevalence was 0.43% (95% CI: 0.35–0.51). We found that HCWs in non-reference hospitals for COVID-19 (odds ratio [OR]: 1.81, 95% CI: 1.23–2.64; P = 0.002) and reference hospitals for COVID-19 (OR: 1.66, 95% CI: 1.06–2.58; P = 0.03) were more likely to be seropositive than HCWs in primary care centres. Regarding professions, nurses (OR: 1.45, 95% CI: 1.07–1.98; P = 0.02), physicians (OR: 1.43, 95% CI: 1.06–1.93; P = 0.02), and administrative, cleaning and security staff (OR: 1.50, 95% CI: 1.09–2.06; P = 0.01) had a statistically higher chance of having a positive serology than laboratory employees. Conclusions: The adjusted overall seroprevalence found in this study indicates a very low prevalence of SARS-CoV-2 among HCWs in Greece. This result is in line with the low incidence of COVID-19 during the first wave of the pandemic and is a direct benefit from the early implementation of lockdown.